Information and Communication Technology to Help Students Create Their Own Books the Dialogic Way - Ivone, Francisca Maria; Jacobs, George M; Santosa, Made Hery (Widya Mandala Catholic University Surabaya, 2020)
The use of Information and Communication Technology (ICT) in language learning allows students to be more engaged and innovative. The present article explores the potential use of technology in the planning, drafting, reviewing, and publishing stages of students’ own book creation. First, the use of digital tools to create books in an interactive and engaging process and format is discussed. Then, the varieties of multimedia books created using ICT are explored. Next, the use of technology for sharing ideas, communicating opinions, collaborating, and reviewing others’ books is explained. The article also describes some collaborative methods students may employ in creating books. Finally, it discusses learners’ development of technology and media literacy in the creation of their own books.